A Global Vector Autoregression Model for the Analysis of Wheat Export Prices. (1st December 2014) - Gutierrez, Luciano; Piras, Francesco; Paolo Roggero, Pier
Abstract : Food commodity price fluctuations have an important impact on poverty and food insecurity across the world. Conventional models have not provided a complete picture of recent price spikes in agricultural commodity markets, and there is an urgent need for appropriate policy responses. Perhaps new approaches are needed to better understand international spill‐overs, the feedback between the real and the financial sectors, as well as the link between food and energy prices. In this article, we present the results from a new worldwide dynamic model that provides the short and long‐run impulse responses of the international wheat price to various real and financial shocks.